Nano/Micro-Assisted Regenerative Medicine - Soo-Hong Lee (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Regenerative medicine is an emerging multidisciplinary field that aims to repair and restore the normal functions of tissues and organs damaged by aging, disease, injury, or congenital disorders. The basic concept of "Nano/Micro-Assisted Regenerative Medicine" is to use advanced nano/micro-technologies, either alone or in combination with specific cells, such as stem cells, to replace, enhance, or regenerate damaged or diseased human tissues or organs. This book introduces promising applications of nano/micro-technologies, such as iron oxide nanoparticles, simvastatin-loaded porous microspheres, graphene-RGD nanoisland composites, bioreducible poly(ethylene glycol)-poly(amino ketal) micelles, reduced graphene oxide-coated biphasic calcium phosphate bone graft material, amorphous nano/micro polyphosphate, cilostazol ophthalmic nanodispersions, carbonic anhydrase-IX anchored albumin-paclitaxel nanoparticles, peptide liposome incorporated citron extracts, turmeric extract-loaded nanoemulsions, and inkjet-printed nanofibrous membrane, in different tissue engineering or cancer treatment applications. In addition, it provides strategies for the further development of this field.